2020
DOI: 10.48550/arxiv.2006.04557
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DMRG on top of plane-wave Kohn-Sham orbitals: case study of defected boron nitride

Abstract: In this paper, we analyze the numerical aspects of the inherently multi-reference density matrix renormalization group (DMRG) calculations on top of the periodic Kohn-Sham density functional theory (DFT) using the complete active space (CAS) approach. Following the technical outline related to the computation of the Hamiltonian matrix elements and to the construction of the active space, we illustrate the potential of the framework by studying the vertical many-body energy spectrum of hexagonal boron nitride (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…We choose a real-space as opposed to a periodic density functional approach to avoid artificial interactions across neighboring supercells which could obscure the defect-defect interactions of interest. Furthermore, it has been shown that realspace electronic structure calculations on hexagonal boron nitride (hBN) nanoflakes can be extrapolated onto periodic calculations [46,47]. The size of the nanoflake, around 220 atoms in total, is chosen such that there are at least 4 unit cells of hBN beyond the boundaries of the localized defect orbitals before termination with passivating hydrogen atoms.…”
Section: Resultsmentioning
confidence: 99%
“…We choose a real-space as opposed to a periodic density functional approach to avoid artificial interactions across neighboring supercells which could obscure the defect-defect interactions of interest. Furthermore, it has been shown that realspace electronic structure calculations on hexagonal boron nitride (hBN) nanoflakes can be extrapolated onto periodic calculations [46,47]. The size of the nanoflake, around 220 atoms in total, is chosen such that there are at least 4 unit cells of hBN beyond the boundaries of the localized defect orbitals before termination with passivating hydrogen atoms.…”
Section: Resultsmentioning
confidence: 99%
“…The subscripted letters in the names of the defect systems are the atoms of the hBN nanoflake that are being replaced, and their substituents CH, C, and V correspond to a carbon atom bonded to a hydrogen atom, a carbon atom, and a vacancy, respectively. To theoretically model the electronic structure of these defect systems, we use the pseudopotential, real-space density functional theory method Octopus [72][73][74], as it has been shown that real-space electronic structure calculations on hexagonal boron nitride (hBN) nanoflakes can be extrapolated onto periodic calculations [75,76]. For the ground state, we use the Perdew, Burke, and Ernzerhof (PBE) generalized gradient approximation exchange-correlation functional [77], and for the excited state calculation, we use a functional based on the local density approximation (LDA) [78,79].…”
Section: Model Defect Systemsmentioning
confidence: 99%